2010
DOI: 10.1073/pnas.0914715107
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and cell intrinsic roles of Gqα signaling in the regulation of innate immunity, oxidative stress, and longevity in Caenorhabditis elegans

Abstract: Signal transduction pathways that regulate longevity, immunity, and stress resistance can profoundly affect organismal survival. We show that a signaling module formed by the G protein alpha subunit, Gqα, and one of its downstream signal transducer phospholipase C β (PLCβ) can differentially affect these processes. Loss of Gqα and PLCβ functions result in increased sensitivity to pathogens and oxidative stress but confer life span extension. Gqα and PLCβ modulate life span and immunity noncell autonomously by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 40 publications
9
45
1
Order By: Relevance
“…PLC can be activated by interaction with α subunits of heterotrimeric Gq proteins, or Gα q (Taylor et al, 1991). Furthermore, previous work showed that the C. elegans Gα q homolog EGL-30 can activate PLCβ homolog EGL-8 for host defense against Pseudomonas aeruginosa or Microbacterium nematophilum infection (Kawli et al, 2010; McMullan et al, 2012). In addition, activation of EGL-30 during fungal infection triggers EGL-8 and Ca 2+ release to activate dual oxidase, or Duox (Zou et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLC can be activated by interaction with α subunits of heterotrimeric Gq proteins, or Gα q (Taylor et al, 1991). Furthermore, previous work showed that the C. elegans Gα q homolog EGL-30 can activate PLCβ homolog EGL-8 for host defense against Pseudomonas aeruginosa or Microbacterium nematophilum infection (Kawli et al, 2010; McMullan et al, 2012). In addition, activation of EGL-30 during fungal infection triggers EGL-8 and Ca 2+ release to activate dual oxidase, or Duox (Zou et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In such pathway, a GPCR-Gα 12 -PLCγ-PKCδ pathway controls a STAT-type transcription factor (Dierking et al, 2011; Ziegler et al, 2009; Zugasti et al, 2014). C. elegans Gα q also has known roles upstream of PLCβ for the regulation of host defense against P. aeruginosa and oxidative stress (Kawli et al, 2010) and for the upregulation of transcription factor DAF-16 in the epidermis during D. coniospora infection (Zou et al, 2013). Furthermore, C. elegans Gα q was recently shown to control both innate immunity and infection avoidance behavior against M. nematophilum (McMullan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The innate immunity in C. elegans is triggered by several signaling cascades, including PMK-1, DAF-16, MPK-1, DKF-2, FSHR-1, and EGL-30 (14,(16)(17)(18)(19)(20)(21). The active role of autophagy in innate immune responses to P. aeruginosa PA14 in C. elegans led us to hypothesize that one of these signaling pathways could mediate autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the following major signaling cascades have been identified as involved in C. elegans defense against pathogenic bacteria: the p38 mitogen-activated protein kinase (MAPK) PMK-1 (16), , the extracellular signal-regulated kinase (ERK) MAPK MPK-1 (14,18), the protein kinase D DKF-2 (19), the G protein-coupled receptor FSHR-1 (20), and the G protein Gqα EGL-30 (21). Here, we investigated the function of autophagy in innate immune responses to P. aeruginosa PA14 in C. elegans.…”
mentioning
confidence: 99%
“…Initial studies did not observe a role for the C . elegans major oxidative stress response transcription factor SKN-1 during infection [34,35], but further work, with additional controls, carried out by two independent laboratories discovered SKN-1 to be protective [32,33]. During infection, SKN-1 activation increases the expression of antioxidants in a BLI-3-dependent manner enhancing survival.…”
Section: Ros Are Signaling Molecules That Induce Protection During Inmentioning
confidence: 99%